Podcasting: tool to develop and reinforce EFL learning - Anali Carolina Rodríguez-Castro; Juanita Catalina Argudo-Serrano (Revista Metropolitana de Ciencias Aplicadas)
This research explored the application of podcasts in the English as a Foreign Language (EFL) teaching context, mainly focused on the development of speaking and listening skills. This could shed light on the impact of ‘Podcasting’ in teaching and learning the mentioned skills. As a really important point of start, it offered basic characteristics, types of podcasts, and the topics which might be used throughout the research, that is why three different groups of students with different language levels (A1, A2, B1), according to the Common European Framework of Reference for Languages (CEFRL), belonging to “Be Free English Academy”, participated in this study, each level has seven learners of different ages; who were evaluated throughout two different months as well as explored the impact ‘Podcasting’ might have on them. This research evaluated the advantages, disadvantages, and contributions of podcasts in EFL classrooms to the development of language skills mainly listening and speaking Also, it examined the effect on the students’ attitudes after the podcasting strategy was implemented. Research in this field helps to understand the outcomes that this “relatively” new technological tool has and its implications in the English learning process.